Desain Web Dashboard Berbasis Pengguna: Menggunakan Design Thinking untuk Meningkatkan Pengelolaan Data - Wahyudi, M. Ilham; Silmina, Esi Putri (Jurnal Informatika Terpadu, 2025)
This study aims to design a user-based web dashboard by applying the Design Thinking methodology to improve data management in organizations. In the digital era, effective data management is crucial for supporting informed decision-making. The Design Thinking method involves five stages: Empathize, Define, Ideate, Prototype, and Test, which focus on understanding user needs. Through interviews and observations, specific user needs were identified, creating a clear problem statement. Innovative ideas were then collected, and a dashboard prototype was developed using Figma. Testing was carried out to assess the effectiveness of the resulting solution. The results indicate that the designed dashboard can improve the ease of use and efficiency in data management. 80% of respondents felt that features such as graphs, tables, and bubble maps helped in data analysis, but some users had difficulty navigating and understanding these features. Therefore, this study recommends further development, such as adding user guides and interactive tutorials, to make the dashboard more user-friendly and relevant to user needs.